Ultranarrow-linewidth stimulated Brillouin scattering with fundamental acoustic waves - Wendao Xu; Maxime Zerbib; Arjun Iyer; Kien Phan Huy; Jean-Charles Beugnot; William H. Renninger (APL Photonics)
Stimulated Brillouin scattering is a well-known nonlinear optical interaction valued for applications including narrow-linewidth lasers, phase conjugation, sensing, and RF-signal processing such as delay lines and filters. While interaction strength and linewidth directly affect device performance, most strongly interacting Brillouin systems have linewidths of many MHz, limited by the high frequency of the participating acoustic waves. By engineering Forward Inter-Modal Brillouin interactions to access the Fundamental Acoustic Modes (FIM-FAM), strong Brillouin coupling can be extended over a wide frequency range, including lower frequencies that support significantly narrower linewidths. In this work, sub-MHz Brillouin linewidths as narrow as 110 kHz are observed in tapered optical fibers with homogeneous waists. Tight confinement of both the optical and acoustic waves yields Brillouin gains over a thousand times higher than traditional backward Brillouin scattering in standard fibers, and a long waist and low-loss transitions enable a Brillouin interaction strength nearly a hundred times greater than prior taper-based FIM-FAM demonstrations. A specific radius and comprehensive polarization control suppress background scattering by over 40 dB relative to the signal. A comprehensive theoretical model is developed accounting for the dynamical behavior of optical and acoustic waves, reproducing qualitative behavior for several experimental configurations. In addition, the dependence of homogeneity of the linewidth is investigated and reveals a route toward further linewidth reduction by controlling phase-matched frequency variations throughout the waist. Extending strongly coupled Brillouin interactions to ultranarrow linewidths with a recipe for fabrication, detailed characterization techniques, and a comprehensive theoretical treatment will benefit high-performance Brillouin-based photonic applications.